A prospective evaluation of breast satisfaction and expectation in preoperative immediate breast reconstruction patients** - Kuroda, Flávia; Urban, Cícero de Andrade; Dória, Maíra Teixeira; Rabinovich, Íris; Lourenço, Mateus Ricardo; Sobreiro, Bernardo; Loureiro, Marcelo (Mastology, 2025)
Breast reconstruction has an important positive contribution to the quality of life of breast cancer patients. However, a large proportion of breast cancer survivors have unmet expectations surrounding reconstruction. This study aimed to delineate factors affecting preoperative native breast satisfaction and expectations with surgery in immediate breast reconstruction (IBR) patients. Methods: This is a prospective cross-sectional trial with breast cancer patients undergoing oncology surgery following breast reconstruction enrolled from 2019 to 2021 at the Hospital Nossa Senhora das Graças in Curitiba, Brazil. Two groups were studied: patients who underwent mastectomy following IBR with implant; and those who underwent breast conservative therapy (BCT) following oncoplastic surgery (OP). All patients completed a patient-reported outcome, the BREAST-Q Breast Reconstruction Expectations Module, prior to surgery. Results: Seventy-nine patients with breast cancer were included: 49 OP and 30 mastectomy following IBR. The mastectomy with IBR implants group had a better satisfaction with their native breast than the OP group (p=0.001). Women in the OP group had higher expectations for breast appearance when clothed than the mastectomy with IBR implant group (p=0.030). Patients aged 50 years and older with a university education or higher level expected that their breast appearance would match almost the same after ten years (p=0.001). Conclusions: Our results highlight the importance of establishing realistic expectations prior to surgery. Understanding which factors affect patients’ satisfaction with native breasts and their expectation toward surgery in the preoperative set could improve preoperative counseling and management of patients’ expectations regarding breast reconstruction.